Pengembangan Sistem Kipas Angin Pintar Berbasis IoT untuk Pemantauan Suhu dan Kelembapan secara Real-Time - Arief, Yoga Sofyan; Akbar, Yuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The increase in indoor temperature and humidity often leads to discomfort and excessive energy consumption in conventional fans operated manually. This study aims to develop a smart fan system based on the Internet of Things (IoT) with adaptive control, capable of monitoring temperature and humidity in real-time and adjusting fan speed automatically or manually via a smartphone application. The system was built using a DHT11 temperature and humidity sensor, a NodeMCU ESP8266 microcontroller, and the Blynk IoT platform as the primary interface. Test results show that the sensor achieved an accuracy of ±0.8°C for temperature and ±3% for humidity, with an average data transmission latency of < 2 seconds and a fan response time of < 1 second. The system operated stably for approximately 1 hours without connection interruptions. By applying adaptive control through hysteresis logic, the system has the potential to reduce energy consumption by dynamically adjusting the fan duty cycle compared to conventional fans. This development contributes to creating an adaptive, comfortable, and energy-efficient indoor environment.